Inspiration and Revelation of the Qur’an and Its Relation to the Bible - Galadari, Abdulla (Religions, 2021)
The Qur’an often compares its own inspiration and revelation with previous scriptures to its audience. However, the Jews and Christians in Late Antiquity had manifold understandings of the inspiration and revelation of scripture. The rabbinic tradition posits various degrees of inspiration behind canonical scriptures: the Torah was dictated by God to Moses, while other prophets had lesser degrees of divine inspiration. Many Christian churches typically held a dual authorship concept, where the human author wrote under the inspiration of a divine author. Many Muslim traditions held various understandings of the agency, or lack thereof, of Muḥammad in the utterances of the Qur’an. Nonetheless, the Qur’an claims that its own inspiration is no different from some biblical books. Since the rabbinic and Christian views differ, it is imperative to understand the Qur’anic concept of itself on inspiration and revelation (waḥy and tanzīl), especially since it compares itself with other scriptures. Additionally, it is argued that the Qur’an’s self-referentiality as a "kitāb" that descends does not necessarily denote a "book" (neither heavenly nor earthly), but an order or commandment, which is more loyal to the root definition.